Recent Trends in Reconfigurable Antennas for Modern Wireless Communication: A Comprehensive Review - Ashish Kumar; Mohammad Aljaidi; Isha Kansal; Kaznah Alshammari; Gifty Gupta; Sami Mohammed Alenezi (International Journal of Antennas and Propagation)
Reconfigurable antennas (RAs) are the key component in the modern wireless communication applications as these antennas have the ability of multifunctional and altered radiating properties in the form of radiation patterns and polarizations. The need for multiple antennas in a single device is becoming more prominent these days due to the increasing applications and user demands in daily life. Consequently, these antennas cover the maximum space in the devices; therefore, to mitigate this problem, RAs are the best solution. This article discusses the various types of RA along with the reconfigurable methods in detail. These types include the frequency, radiation pattern, polarization, and compound RAs, and methods include the electrical (with switches), mechanical, optical, and material change. Based on the requirement and application, proper methods have been chosen by the authors to achieve the reconfigurability in the antennas. The RAs find applications in various sectors including terrestrial and satellite communications, vehicular communication due its movement in rural and urban areas, and cognitive radio.